2018
DOI: 10.1186/s12879-018-3019-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes and factors affecting unsuccessful outcome among new pulmonary smear positive and negative tuberculosis patients in Anqing, China: a retrospective study

Abstract: BackgroundMonitoring the treatment outcomes of tuberculosis and determining the specific factors associated with unsuccessful treatment outcome are essential to evaluate the effectiveness of tuberculosis control program. This study aimed to assess treatment outcomes and explore the factors associated with unsuccessful outcomes among new pulmonary smear positive and negative tuberculosis patients in Anqing, China.MethodsA nine-year retrospective study was conducted using data from Anqing Center for Diseases Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
46
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 30 publications
13
46
3
3
Order By: Relevance
“…TB cases in our study cohort were mostly adult males, a trend similarly observed worldwide [1]. We also found that being males and older age were significantly associated with unsuccessful TB treatment outcomes and all-cause mortality, concurring with findings reported elsewhere [12,32,33]. Urban and rural places of residence, as well as varying levels of education, were well represented with fair distribution among patients in our study cohort.…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…TB cases in our study cohort were mostly adult males, a trend similarly observed worldwide [1]. We also found that being males and older age were significantly associated with unsuccessful TB treatment outcomes and all-cause mortality, concurring with findings reported elsewhere [12,32,33]. Urban and rural places of residence, as well as varying levels of education, were well represented with fair distribution among patients in our study cohort.…”
Section: Plos Onesupporting
confidence: 90%
“…Worldwide, studies had investigated on TB treatment outcomes by looking into factors that were associated with unsuccessful treatment outcomes as well as mortality among TB patients [8][9][10][11][12][13]. Important predictive factors reported include patients' sociodemographic characteristics (age, sex, education levels, employment), underlying comorbidities such as diabetes mellitus (DM) and human immunodeficiency virus (HIV) infection as well as TB disease profile/ factors (sputum and radiological findings, site of TB infection, history of previous TB treatment).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multivariate logistic regression revealed that pretreatment weight < 40 kg, older age (> 45 years), and HIV infection independently associated with unsuccessful treatment outcomes. Independent association of older age (> 30 years [28], retreatment and HIV co-infected [26] with unfavorable treatment outcome was also reported by others. Thus, TB patients with pretreatment weight < 40 kg, older age (> 45 years), and HIV infected need special social and economic support, early diagnosis and close monitoring throughout their treatment period in the refugee camps in Ethiopia.…”
Section: Discussionsupporting
confidence: 69%
“…In contrary, according to a study done in Nigist Eleni Mohammod General Hospital Hosanna, Ethiopia; those patients having smear-positive Pulmonary TB were more likely to had poor treatment outcomes compared with those patients having extra-pulmonary TB [7]. But, the other studies done in other parts of Ethiopia [15,20] and China [27] reported as there is no significant difference between treatment success rate and type of TB. According to studies conducted at Jinka General Hospital [21], Afar [28] and another study done by Kefale et al at Southwest Ethiopia [29]; TB/HIV co-infection was found to be a predictor for unsuccessful treatment outcome, which is similar to the present study.…”
Section: Discussionmentioning
confidence: 93%